Análise diagnóstica de cursos de graduação em engenharia mecânica à luz das novas diretrizes curriculares - Madalozzo, Yohanna (Universidade Federal de São Carlos, 2022)
Although engineering and engineering education existed for centuries; standardization started just a few decades ago. In Brazil, the first engineering course emerged in 1792, yet only in 1976 appeared initial curriculum guidelines that, in 2002, were replaced for national regulations. Those regulations are the foundation for pedagogical projects nowadays. However, several projects had already shown some aspects of the curriculum guidelines launched in 2019, where the aptitudes were more meaningful than the content. This work delivers a diagnostic analysis of various pedagogical projects of mechanical engineering courses for the sake of new curriculum guidelines to envision the correlation between a manifold of projects and, accordingly, the subjects, students' performance, and universities in official assessments. The correlation can be validated using the method of Partial Least Squares - Structural Equation Modeling or PLS-SEM. Some templates used keywords from projects and the National Assessment System of University Education to understand if the correlation between variables was valid. The results had shown that only one of the templates achieved a tolerable validation: a template that only considered pedagogic projects published from 2013. Other templates bring several noteworthy inputs to understand topics that need improvement for future projects.
Diagnose analysis of undergraduate courses on mechanical engineering facing new curricular guidelines
Keywords: Projetos pedagógicos; Ensino de engenharia; Avaliação da educação superior; PLS-SEM; ENGENHARIAS::ENGENHARIA MECANICA